DARI PENOLAKAN KE PENERIMAAN STRATEGI EDUKASI TERPADU DALAM PROGRAM KB IMPLANT DAN IUD - Wijaya, Indra (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2026)
ABSTRACT The low level of community acceptance of Long-Acting Reversible Contraceptive Methods (LARCs), particularly contraceptive implants and intrauterine devices (IUDs), remains a challenge in the implementation of the Family Planning Program due to the persistence of myths, medical misconceptions, and religiously based doubts. This study aims to analyze the process of attitude change from rejection to acceptance of contraceptive implants and IUDs through the implementation of an integrated educational strategy. The study employed a qualitative approach with a reflective case study design conducted in family planning program target areas in Banjarmasin City, involving couples of reproductive age, prospective and current contraceptive users, religious leaders, and healthcare providers selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed thematically with triangulation to ensure data credibility. The findings indicate that the integration of medical education and religious clarification effectively reduces myths, enhances understanding, and builds community trust in contraceptive implants and IUDs. Changes in attitudes were reflected in increased openness and willingness to use LARCs, as indicated by the achievement of new LARC user ratios exceeding program targets. The study concludes that acceptance of LARCs is strongly influenced by the alignment of educational approaches with the social and religious context of the community, suggesting that integrated educational strategies have the potential to serve as a contextual and sustainable alternative model for the implementation of family planning programs. ABSTRAK Rendahnya penerimaan masyarakat terhadap Metode Kontrasepsi Jangka Panjang (MKJP), khususnya KB implant dan intrauterine device (IUD), masih menjadi tantangan dalam Program Keluarga Berencana (KB) akibat kuatnya mitos, miskonsepsi medis, dan keraguan berbasis pemahaman keagamaan. Penelitian ini bertujuan menganalisis perubahan sikap masyarakat dari penolakan menuju penerimaan KB implant dan IUD melalui penerapan strategi edukasi terpadu. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus reflektif di wilayah binaan program KB Kota Banjarmasin, melibatkan pasangan usia subur, calon dan akseptor KB, tokoh agama, serta tenaga kesehatan yang dipilih secara purposive. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan dokumentasi, kemudian dianalisis secara tematik dengan triangulasi untuk menjaga keabsahan data. Hasil penelitian menunjukkan bahwa integrasi edukasi medis dan klarifikasi keagamaan mampu mengurangi mitos, meningkatkan pemahaman, serta membangun kepercayaan masyarakat terhadap KB implant dan IUD. Perubahan sikap tercermin dari meningkatnya keterbukaan dan kesediaan menggunakan MKJP yang ditunjukkan oleh capaian rasio peserta KB baru yang melampaui target. Simpulan penelitian menegaskan bahwa penerimaan MKJP sangat dipengaruhi oleh kesesuaian pendekatan edukasi dengan konteks sosial dan religius, sehingga strategi edukasi terpadu berpotensi menjadi model alternatif yang kontekstual dan berkelanjutan dalam pelaksanaan program KB.